A Phase 1 Study of SLC-0111, a Novel Inhibitor of Carbonic Anhydrase IX, in Patients With Advanced Solid Tumors. (July 2020) - McDonald, Paul C.; Chia, Stephen; Bedard, Philippe L.; Chu, Quincy; Lyle, Michael; Tang, Liren; Singh, Madhu; Zhang, Zaihui; Supuran, Claudiu T.; Renouf, Daniel J.; Dedhar, Shoukat
Abstract : Objectives: SLC-0111 is an ureido-substituted benzenesulfonamide small molecule inhibitor of carbonic anhydrase IX. The objectives of this first-in-human Phase 1 study were to determine the safety and tolerability of SLC-0111 in patients with advanced solid tumors and to establish the recommended Phase 2 dose for future clinical investigations. Materials and Methods: Using a 3+3 design, dose escalation started at 500 mg oral daily dosing of SLC-0111 in cohort 1 and increased to 1000 and 2000 mg in cohorts 2 and 3. Drug-related adverse events (AEs) were monitored to determine safety and tolerability. Pharmacokinetic analyses assessed plasma concentrations of single and repeated doses of SLC-0111. RECIST 1.1 criteria were used to assess disease progression. Results: No dose-limiting toxicities were reported and patients dosed at ⩽1000 mg exhibited fewer drug-related AEs ≥ grade 3 and fewer AEs such as nausea and vomiting, compared with the 2000-mg cohort. Forty-one percent of patients experienced dose interruptions or discontinuation and the majority (71%) of these occurred in the 2000-mg cohort. Mean C max and AUC(0-24) values for single doses were similar at the 1000-mg and 2000-mg dose levels. Mean T max and T 1/2 values of SLC-0111 were similar after single and repeated dosing. Power-law analysis of C max and AUC0-24 showed that exposure to SLC-0111 was generally dose proportional. No objective responses were observed, but stable disease >24 weeks was observed in 2 patients. Conclusions: SLC-0111 was safe in patients with previously treated, advanced solid tumors. The safety and pharmacokinetic data support 1000 mg/d as the recommended phase 2 dose for SLC-0111. Abstract : Supplemental Digital Content is available in the text.